PLANT SPECIES DESCRIBED BY GEORGE BENTHAM AND JOSEPH HOOKER IN HENDERSON AND HUME'S LAHORE TO YĀRKAND - Turner, I. M. (Edinburgh Journal of Botany, 2016)
Five plant species (Apocynum hendersonii Hook.f. (Apocynaceae), Deyeuxia anthoxanthoides Munro ex Hook.f. (Gramineae), Hololachna shawiana Hook.f. (Tamaricaceae), Iphiona radiata Benth. (Compositae) and Saussurea ovata Benth. (Compositae)) were described from specimens collected by George Henderson on the political mission to Yarkand (now in Xinjiang Province of China) in 1870. The names, with accompanying descriptions and illustrations, appeared in Lahore to Yārkand by Henderson and A. O. Hume. An exact publication date of 1 April 1873 is established for this work of relevance to avian as well as plant taxonomy. The typification of the plant species names to specimens in the Kew herbarium is reviewed. Four new lectotypes are proposed.
Keywords: Central Asia; George Bentham; George Henderson; Joseph Hooker; lectotype; Xinjiang